ORGANIZATIONAL CULTURE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR: THE MEDIATING ROLE OF LEARNING ORGANIZATIONS AND ORGANIZATIONAL COMMITMENT - Yudi Siswadi; Jufrizen Jufrizen; Jasman Saripuddin; Salman Farisi; Maya Sari (Faculty of Economic and Business, University of Pasundan, 2023)
This study aims to find out how the Organizational Citizenship Behavior Model Based on Organizational Culture is mediated by Learning Organizations and Organizational Commitment. The sample size in this study was tailored to the analytical model used, namely Structural Equation Modeling utilizing the Maximum Likelihood Estimate (MLE) estimation model requires 100-200 samples. As a result, the sample size for this study was 200 permanent lecturers at Private Universities in North Sumatra. The data analysis method used Structural Equation Modeling. The results showed that Organizational Culture, Learning Organization, and Organizational Commitment had a significant positive effect on Organizational Citizenship Behavior. Organizational Culture and Learning Organization had a significant positive effect on Organizational Commitment. Learning organizations mediated positively the effect of Organizational Culture on Organizational Citizenship Behavior and Organizational Commitment mediate the effect of Organizational Culture on Organizational Citizenship Behavior.